Analisis Pengembalian Pendapatan Pada Pelaporan Keuangan Dan Relevansi Nilai Informasi Akuntansi - Herru Soerjono; Mira Ismirani Fudsyi; Sakti Muda Nasution; Budi Lesmana; Rumaizha, Riri (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This research aims to find the relationship between stock returns and profit levels and changes in profits, analyze financial reporting income returns and evaluate accounting values. Income return analysis in financial reporting is the process of evaluating a company's income performance by looking at various factors that influence it, including the income return itself. The purpose of the analysis is to understand sources of income, sales effectiveness, and potential problems that can affect future income. The research method used is an incremental relative association approach in order to determine changes in the relevance of the value of accounting information with financial reporting. The Easton and Harris model is implemented in this research by collecting accounting data over several time periods, as well as observing companies listed on the stock exchange. Hypothesis testing uses econometric tests and multivariate panel regression. The results of the reaserch showed a decrease in the relevance of the value of income returns in financial reporting. The contribution of this researchis the documentation of changes in value relevance in the financial reporting process. The results of the value relevance are only based on the return model, not analyzing the price model.